Strategi Peningkatan Pendapatan Asli Daerah di Kota Malang (Studi pada Retribusi Sampah dan Layanan Kebersihan - Farah Wulandari W. P.; Ferry Prasetyia (Jurnal Aplikasi Manajemen, 2011)
The aim of this paper is to formulate a strategy to enhance the local revenue especially from the garbage disposal and cleaning charges in Malang city. Using Quantitative Strategies Planning Matrix (QSPM) as a tool of strategic management, the result shows that there are two strategies that can be used to enhance local revenue such as intensive and integrative strategy. Intensive strategies can be done through revising the garbage disposal and cleaning charges law regulation in Malang city; improving the collection system; and improving the calculation of garbage disposal and cleaning potential charges. In the other hand, integrative strategies can be implemented through improving the monitoring of disposal and cleaning charges collection; optimizing the socialization process by social organization; and optimizing the monitoring of local legislative.Keywords: Garbage disposal and cleaning charges, Strategic Management, and QSPM